Analisis GC-MS ekstrak tanaman terfermentasi (ETT) dari kulit buah jengkol (Pithecellobium jiringa Prain) - Refilda Suhaili; Lucy Prima Ardi; Emil Salim; Mai Efdi (CHEMPUBLISH JOURNAL, 2020)
Analysis of active compounds in fermented plant extract (FPE) from the ngapi nut peel using Effective Microorganism-4 (EM-4) has been done by Gas Chromatography-Mass Spectroscopy (GC-MS). There were 88 compounds found in fermented plant extract, the major content with the area above 1% were 7 compounds such as succinic acid; ethyl hydrogen succinate; 1,2,3-benzetriol; 3,3-dimethylhexanal; L-proline, 1-methyl-5-oxo-methyl ester; 3-methoxycinnamic acid and hexadecanoic acid. Based GC-MS analysis, fermented plant extract indicated that several compounds that have potential as biopesticides.